Incorporating corporate social responsibility criteria into the Barclays bank lending appraisal process - Considine, Kevin (Cranfield University, 2003)
In response to growing corporate power, corporate social responsibility (CSR) is increasing public demand that businesses should demonstrate greater responsibility for managing their impact on society beyond simply paying taxes and complying with regulations. Critical to this debate are commercial banks, which through the action of lending, play a pivotal role in society as financial intermediaries, and therefore, it is argued have an extraordinary potential to further sustainability. The thesis, a case study, examines the feasibility for incorporating CSR criteria as part of the lending appraisal process at Barclays Bank. To begin, the thesis examines the literature on CSR and assesses the theory, application and reliability of this new and growing financial risk factor. For the methodology, the study adopts a process of engagement with a pre-selected group of Barclay’s stakeholders to evaluate the issues key to the debate. Supporting this process of stakeholder engagement, a wider secondary stakeholder group was surveyed to assess the validity of Barclays’ stakeholder responses. To assist the research, an analytical framework of the CSR appraisal process was constructed. The results show correlation between the two stakeholder groups, illustrating not only the objectivity of the stakeholders put forward by Barclays but also the degree of commonality on societal and ethical issues amongst representatives from various organisations. The findings further illustrate that banks are being driven to adopt CSR by a combination of risk factors. Finally, the study puts forward recommendations on facilitating CSR for the lending appraisal process. It draws upon new framework guidelines for CSR and existing environmental credit risk polices and procedures, but in addition, presents new arguments that reflect the opinions of the stakeholder process.